3D bioprinting of multifunctional alginate dialdehyde (ADA)–gelatin (GEL) (ADA-GEL) hydrogels incorporating ferulic acid - Bider, Faina; Miola, Marta; Clejanu, Corina Elena; Götzelmann, Johanna; Kuth, Sonja; Vernè, Enrica; Basu, Bikramjit; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2024)
The present work explores the 3D extrusion printing of ferulic acid (FA)-containing alginate dialdehyde (ADA)–gelatin (GEL) scaffolds with a wide spectrum of biophysical and pharmacological properties. The tailored addition of FA (≤0.2 %) increases the crosslinking between FA and GEL in the presence of calcium chloride (CaCl2) and microbial transglutaminase, as confirmed using trinitrobenzenesulfonic acid (TNBS) assay. In agreement with an increase in crosslinking density, a higher viscosity of ADA-GEL with FA incorporation was achieved, leading to better printability. Importantly, FA release, enzymatic degradation and swelling were progressively reduced with an increase in FA loading to ADA-GEL, over 28 days. Similar positive impact on antibacterial properties with S. epidermidis strains as well as antioxidant properties were recorded. Intriguingly, FA incorporated ADA-GEL supported murine pre-osteoblast proliferation with reduced osteosarcoma cell proliferation over 7 days in culture, implicating potential anticancer property. Most importantly, FA-incorporated and cell-encapsulated ADA-GEL can be extrusion printed to shape fidelity-compliant multilayer scaffolds, which also support pre-osteoblast cells over 7 days in culture. Taken together, the present study has confirmed the significant potential of 3D bioprinting of ADA-GEL-FA ink to obtain structurally stable scaffolds with a broad spectrum of biophysical and therapeutically significant properties, for bone tissue engineering applications.
CRIS-Team Scopus Importer:2024-01-05
Keywords: 3D bioprinting; Alginate; Phytotherapeutic agents